IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI DENGAN MODEL PROJECT BASED LEARNING PADA MATA PELAJARAN IPAS KELAS VI SEKOLAH DASAR - Oktavia Nila Permata; Tri Sutrisno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The success of learning is determined by the teacher's ability to create relevant learning experiences that are in accordance with the diversity of potential and interests of students in the class. The purpose of this study was to describe the implementation of differentiated learning combined with the project based learning (PjBL) model on the material exploring the solar system in the subject of science for grade VI of SDN Wonokerso 1 Sragen. This study was conducted using a descriptive qualitative approach, where data were collected through direct observation, in-depth interviews, and documentation. The focus of this study was on three main stages of differentiated learning, namely the planning stage, the implementation stage, and the learning evaluation stage. The findings demonstrated that planning was carried out by analyzing students' individual learning needs, including learning styles, interests, and readiness levels as the basis for developing adaptive differentiation strategies. The PjBL model at the implementation stage provides a learning framework that encourages students to complete real projects through six structured phases that have been proven to increase student engagement, collaboration, and conceptual understanding. The evaluation stage was carried out formatively and summatively, including assessment of the process, project products, and learning reflections that were adjusted to the students' learning profiles. The main supporting factors were teacher readiness, student participation, and the availability of educational materials and media. In the meantime, the obstacles found included time constraints and gaps in ability between students. Overall, this approach has proven effective in encouraging student engagement, deepening conceptual understanding, and developing their critical thinking skills during science learning in a more meaningfully and contextually.